The Family creative workshop : carryalls, cartoons, carving, casting, ceramics, cheeses and churning, christmas and celebration, collages and assemblages, colonial crafts, colour psychology, confections and comfits, cosmetics - Bragdon, Allen Davenport (Plenary Publications International, 1975)
128 p. : il.; 27 cm.